Determinants of Company Value in Mining Firms: An Empirical Analysis - Dewi, Varia; Savitri, Dhian Andanarini Minar (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: The purpose of this study is to determine the effect of sustainability reports, capital structure, and cash flow volatility on company values for mining companies in the energy and basic material sectors listed on the Indonesia Stock Exchange in 2021-2023 using investment opportunity set as a moderation. Methodology:Â The subjects of the study were mining companies in the energy and raw materials sector listed on the Indonesia Stock Exchange (IDX) in 2021-2023. There is a lot of data so purposive sampling is needed to filter the data needed and processed using multiple linear regression and Moderating Regression Analysis Results: Investment opportunity set can strengthen the influence of sustainability report, capital structure and cash flow volatility on company values. Finding: Sustainability report and capital structure have a positive effect on firm value while cash flow volatility has a negative effect on firm value. Investment opportunity set moderates the effect of sustainability report and capital structure on company values, but Investment opportunity set does not moderate the effect of cash flow volatility on company values. Novelty: This study uses the energy and basic materials sectors because these sectors have experienced a fairly high increase in investment value which results in high capital requirements and high cash flow volatility. Originality: This study provides a detailed explanation of the role of investment opportunity set as a moderating tool for the influence of sustainability reports, capital structure and cash flow volatility on company values. Conclusion: By using investment opportunity sets, the influence of sustainability reports and capital structures on company values can be increased, but according to research results, it turns out that investment opportunity sets cannot increase the influence of cash flow volatility on company values. Type of paper: Empirical Research Paper